A comparison of pregnancy prevention programmes in Europe. (April 2014) - Crijns, Ineke; Zomerdijk, Inge; Sturkenboom, Miriam; de Jong-van den Berg, Lolkje; Straus, Sabine
<x xml:space="preserve">Abstract</x> Background: Pregnancy prevention programmes (PPP) can be imposed by regulatory authorities to minimise the risk of exposure to teratogenic drugs during pregnancy, thus preventing congenital anomalies. The objective of this study was to explore the reasons to request PPPs in the EU and the elements that they included. Methods: For the seven drugs with a PPP, the Summary of Product Characteristics (SmPC) and publicly available assessment reports at the EMA website were used to obtain data. Results: Five of the seven drugs obtained a PPP based on an established or expected high teratogenic risk in humans. Similarities in the PPPs were: pregnancy tests both before and monthly during drug use; contraceptive use and pregnancy prevention counselling. Differences regarded educational materials, restricted drug supply, continuation of contraceptive use and pregnancy tests after treatment. The last two differences could be explained by pharmacological characteristics of the drug. Conclusions: The reason for requesting a PPP is not always clearly defined and variation in risk minimisation measures for teratogenic drugs exists. There is a need for regulatory guidance on proper judgement to request for a PPP and its development. Knowledge on the benefits and burden of PPPs in clinical practice is necessary to optimise PPPs.